2020
DOI: 10.1111/cas.14385
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic characterization of lysine acetyltransferases in human cancer and their association with clinicopathologic features

Abstract: The dynamic and reversible acetylation of protein, catalyzed by lysine acetyltransferases (KATs, also known as HATs) and deacetylases, plays critical roles in a wide range of biological processes including transcriptional regulation, DNA damage repair, signal transduction, stem cell self-renewal, cellular metabolism, and biological rhythm. Lysine acetyltransferases are a highly diverse group of enzymes. Under the action of KATs, the acetyl group from acetyl coenzyme A is co-or posttranslationally attached to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…A second observation was that some NATs were deregulated in multiple tumour types (e.g., NAA10, NAA20, and NAA40), while others in few or none (e.g., NAA30, NAA60, NAA35). Consistent with the findings here, some of the NAT-tumour associations uncovered by the cancer vs. normal RNA expression comparison have been reported previously, such as NAA10 in lung, colorectal, liver, and breast cancer [ 18 , 19 ], NAA20 in liver [ 16 ]. We have also shown potential mechanistic links between altered DNA methylation and the deregulation of NATs in some tumours.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A second observation was that some NATs were deregulated in multiple tumour types (e.g., NAA10, NAA20, and NAA40), while others in few or none (e.g., NAA30, NAA60, NAA35). Consistent with the findings here, some of the NAT-tumour associations uncovered by the cancer vs. normal RNA expression comparison have been reported previously, such as NAA10 in lung, colorectal, liver, and breast cancer [ 18 , 19 ], NAA20 in liver [ 16 ]. We have also shown potential mechanistic links between altered DNA methylation and the deregulation of NATs in some tumours.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to a collection of well-established cancer genes on which we performed the same analyses, genomic alterations of NATs are considerably lower (TP53—36%; PTEN—12%; KRAS—9%; MYC—9%; RB1—7%). We also compared NATs to 34 KATs, as defined in a recent report [ 19 ], which showed that the former are, on average, affected at a lower frequency ( Figure S1 ), and several KATs were altered in 4–6% of samples (e.g., KAT6, EP300, TAF1). On average, therefore, NAT genes are characterised by a low prevalence of mutational activity across all tumour types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ) [ 173 ]. AMPK phosphorylates and inhibits acetyl-CoA carboxylase (ACC), thereby increasing the level of acetyl-coA in tumor cells [ 174 ]. And since acetyl-CoA is the substrate for all KATs, lysine acetyltransferase activity is increased [ 175 ].…”
Section: Influence Of Intracellular Metabolites On Hif-α Stability Thmentioning
confidence: 99%
“…Another intriguing, albeit unvalidated interaction, that we discovered was EP300-TAF1(Log2NID score = 2.39). Both of these TFs are well known lysine acetyltransferases and are responsible for activating and regulating transcription of several TGs and were also found to have the highest frequency of oncogenic mutations among all the other lysine acetyltransferases [40]. The Log2NID scores for all pairwise TRMs are shown in the form of a heat-map in the Figure 2C (all scores are available in Supplementary table S3B).…”
Section: Interaction Effects Aided the Detection Of Well-known And Novel Transcription Factor Regulatory Modulesmentioning
confidence: 99%